2011
DOI: 10.1080/17461391.2010.546431
|View full text |Cite
|
Sign up to set email alerts
|

Hand–arm strength and endurance as predictors of climbing performance

Abstract: The aims of this study were to examine training characteristics, body composition, muscular strength, and endurance in sport climbers, and to demonstrate the relationship among these components by means of structural equation modelling. Altogether, 205 sport climbers (136 males, 69 females), with a performance RP (red point) of grade 4 to 11 on the Union Internationale des Association d'Alpinisme (UIAA) scale, took part in the study. The proposed structural model, with latent variable handÁarm strength and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 21 publications
4
94
0
14
Order By: Relevance
“…Finger flexor endurance has been found to be closely related to lead climbing performance (Baláš, Pecha, Martin & Cochrane, 2012); whilst boulderers have been found to have greater relative finger flexor strength and rates of force development than lead climbers (Fanchini et al, 2013;Michailov et al, 2009). It is assumed that different forearm muscle adaptations are related to bouldering and lead climbing training.…”
Section: Introductionmentioning
confidence: 99%
“…Finger flexor endurance has been found to be closely related to lead climbing performance (Baláš, Pecha, Martin & Cochrane, 2012); whilst boulderers have been found to have greater relative finger flexor strength and rates of force development than lead climbers (Fanchini et al, 2013;Michailov et al, 2009). It is assumed that different forearm muscle adaptations are related to bouldering and lead climbing training.…”
Section: Introductionmentioning
confidence: 99%
“…Again we see wide discrepancies between studies and this can be very problematic for making comparison between studies (Schoeffl et al, 2004;Fryer et al, 2012;Baláš, et al, 2012;Donath et al, 2013;Fanchini et al, 2013;Green, Draper & Helton, 2013;Schöffl et al, 2013). In addition to the normal data collected such as age, gender, body mass and height, to better inform readers of future research papers and to facilitate comparison between studies a number of regular characteristics should be reported by authors.…”
Section: Climber Characteristics: Capturing the Groupmentioning
confidence: 99%
“…For example, Baláš, J. et al [7], who studied body composition, muscular strength and endurance of sport mountaineers, determined presence of correlations between these components. Authors outlined the most informative indicators, which included strength of grab, hanging on bent arms and fingers, content of fat, rock climbing experience (dispersion 97%).…”
Section: Introductionmentioning
confidence: 99%